Asupan protein, kalsium dan fosfor pada anak stunting dan tidak stunting usia 24-59 bulan - Endah Mayang Sari; Mohammad Juffrie; Neti Nurani; Mei Neni Sitaresmi (Minat S2 Gizi dan Kesehatan, Prodi S2 IKM, FK-KMK UGM, 2016)
Background: Indonesia is one of developing country which still facing a serious problem concerning stunting. Causes of stunting is a complex things, one of the cause is protein intake which is have effect on the level plasma insulin growth factor I (IGF-I), protein bone matrix and growth factor, also calcium and phosphorus that has an important role in bone formation. One of the province in Indonesia which has stunting prevalence above level of National prevalence is West Borneo. Pontianak as the capital city of West Borneo is still facing serious problem concerning stunting and the low level of food security.Objective: Analyze protein, calcium and phosphorus intake of stunting and non stunting children aged 24-49 months in Pontianak.Method: The study was an analytical observational with cross sectional design. Samples of the study were children aged 24-59 months in the districts of East Pontianak and North Pontianak, West Borneo, as much as 90 samples have been chosen by using simple random sampling technique. The research was conducted from July - August 2015. Statistical analysis was performed by using chi square and t-test.Results: Protein, calcium and phosphorus intake are lower to the stunting compare to non stunting children (p<0,05). Stunting prevalence of lower protein group is higher 1,87 times than adequate protein intake group. Stunting prevalence of low calcium intake group is higher 3,625 times than adequate calcium intake group. Moreover, the stunting prevalence of low phosphor intake group is higher 2,29 times than adequate phosphor intake group.Conclusion: Protein, calcium and phosphor intake significant lower to the stunting compare to non stunting children aged 24- 59 months in Pontianak.